A Policy Analysis of Islamic Education Budget in Indonesia - Choirul Mahfud (Edukasia Islamika, 2019)
Budget policies for Islamic education in contemporary Indonesia, especially in the post-New Order era, are still within the authority of the management of the Ministry of Religious Affairs (MORA) of the Republic of Indonesia. In terms of quantity, the amount of budget obtained is still in the low category compared to the national education budget received by the Ministry of Education and Culture and the Ministry of Research, Technology, and Higher Education. Moreover, the budget received by the MORA is not all for the implementation of Islamic educational institutions but also for other non-Islamic educational institutions which are the responsibility of the ministry. Therefore, this paper discusses the policies of the Islamic education budget in Indonesia and the impacts of these policies on the implementation and sustainability of the quality of Indonesia’s Islamic education. This paper exposes that Islamic education policies are always placed at a crossroads. In this context, the Islamic education budget policy is face to face and even contrasted with other policies. The problems with the political policies of the education budget, including those in the Islamic education budget policy in contemporary Indonesia, still need to be continuously monitored, evaluated, and implemented in relation to existing policies to optimize while providing better solutions and contributions.